Durich Chiampells "Topographie" als Apologie und Inszenierung Rätiens - Caduff, Gian Andrea (Zwingliana, 2015)
Durich Chiampell’s (c. 1510 – c. 1582) "Raetiae alpestris topographica descriptio" deals with the geography of the Republic of the Three Leagues – today the region of Graubünden – in a manner influenced to such a high degree by rhetorical principles that it is rather a mise-en-scène constructed to transmit a certain view of his subject rather than objective knowledge. The article shows this in the chosen examples relating to geography and history. The criticism he faced by his orderers in Zurich were refuted by Chiampell with arguments drawn from contemporary historiography.